Preleukemic hematopoietic hyperplasia induced by Moloney murine leukemia virus is an indirect consequence of viral infection. - Brightman, B K (1990)
We previously showed that neonatal mice inoculated with Moloney murine leukemia virus (M-MuLV) exhibit a preleukemic state characterized by splenomegaly and increased numbers of hematopoietic progenitors. An M-MuLV variant with greatly reduced leukemogenic potential, Mo+PyF101 M-MuLV, does not generally induce this preleukemic state. In order to investigate the mechanism involved in M-MuLV induction of preleukemic hyperplasia, we tested the CFU-mixed myeloid and erythroid (CFUmix) from M-MuLV- and Mo+PyF101 M-MuLV-inoculated mice for the presence of virus by antibody staining and for the release of infectious virus. The majority of CFUmix colonies from both M-MuLV- and Mo+PyF101 M-MuLV-inoculated mice contained infectious virus even though M-MuLV-inoculated mice showed elevated levels of CFUmix while the Mo+PyF101 M-MuLV-inoculated mice did not. This indicates that direct infection of hematopoietic progenitors was not sufficient to induce hyperplasia. Rather, hematopoietic hyperplasia may result indirectly from infection of some other cell type.